2006
DOI: 10.1111/j.1365-2427.2006.01582.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of phytoplankton groups in lakes using new pigment ratios – a comparison between pigment analysis by HPLC and microscopy

Abstract: 1. Pigment analysis by high-performance liquid chromatography (HPLC) combined with data analysis using the CHEMTAX program has proven to be a fast and precise method for determining the abundance of phytoplankton groups in marine environments. To determine whether CHEMTAX is applicable also to freshwater phytoplankton, 20 different species of freshwater algae were cultured and their pigment/chlorophyll a (Chl a) ratios determined for exponential growth at three different light intensities and for stationary gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
99
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 23 publications
14
99
4
1
Order By: Relevance
“…Woitke et al (1996) found a range of 0.35-0.63 and Schlu¨ter et al (2006) 0.39-0.72 in the FUCO:chl a ratio in diatom cultures, thus corresponding rather well to the ratio we calculated from our freshwater data (0.49-0.9). Apart from a light-induced 'fucoxanthin cycle', which seems to operate in some specific haptophyte species (Stolte et al, 2000;Rodrıguez et al, 2006), fucoxanthin is generally considered as a light-harvesting pigment.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Woitke et al (1996) found a range of 0.35-0.63 and Schlu¨ter et al (2006) 0.39-0.72 in the FUCO:chl a ratio in diatom cultures, thus corresponding rather well to the ratio we calculated from our freshwater data (0.49-0.9). Apart from a light-induced 'fucoxanthin cycle', which seems to operate in some specific haptophyte species (Stolte et al, 2000;Rodrıguez et al, 2006), fucoxanthin is generally considered as a light-harvesting pigment.…”
Section: Discussionsupporting
confidence: 52%
“…Although the calculation procedure allows for adjustment of the ratios within a userdefined interval, these initial values can influence the final biomass estimates and may be critical in providing correct quantitative phytoplankton assessment. Typical ratios have been given in the literature from cultures of marine (Jeffrey et al, 1997) and, to a lesser extent, for freshwater algae (Nicklisch & Woitke, 1999;Schlu¨ter et al, 2006). A recent paper by Latasa (2007) described a method to reduce processing errors which may be related to wrong estimates of initial ratios: repeating CHEMTAX processing in successive runs, using the output from each run as the input for the next one, the pigment ratios generally adjust automatically towards the true value, improving initial pigment ratio values and, therefore, biomass estimates.…”
Section: Pigment Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Because carotenoid:Chl a ratios within phytoplankton communities might be expected to vary depending upon species composition, cell physiological state, irradiance, etc., the data set was divided into annual and transect subsets, prior to independent CHEMTAX calculations (Mackey et al 1998;Schlüter et al 2000). CHEMTAX calculations are sensitive to the initial carotenoid:Chl a ratios identified for each group; as such, initial ratios were chosen from those previously derived for and/or applicable to Great Lakes phytoplankton Schlüter et al 2006). To further minimize error arising from ratio variation, data subsets were assessed independently using the initial ratio matrix and an additional 59 matrices generated randomly as the product of the initial values and a randomly determined factor (F):…”
Section: Biological Parametersmentioning
confidence: 99%
“…ChemTax, a matrix factorization program, was used to calculate the relative abundances of major algal groups in the water samples from the HPLC photopigment data [52,53]. For ChemTax, an iterative scheme [54] was followed using the initial pigment ratios from published ratios [55,56]. The ChemTax analysis revealed the relative abundance of seven major algal groups including cyanobacteria, euglenophytes, chlorophytes, dinoflagellates, cryptophytes, diatoms and chrysophytes.…”
mentioning
confidence: 99%